An Income Approach to Accounting Theory (Book). - Zeff, Stephen A.; Stone, Williard E. (The Accounting Review, 1964)
Reviews the book "An Income Approach to Accounting Theory: Readings and Questions," edited by Sidney Davidson, David Green, Charles T. Horngren and George H. Sorter.